Spectroscopic Study of Jet‐cooled Indole‐3‐carbinol by Thermal Evaporation. (28th September 2016) - Moon, Cheol Joo; Kim, Eunbin; Min, Ahreum; Ahn, Ahreum; Seong, Yeon Guk; Choi, Myong Yong
Abstract :